2006
DOI: 10.1254/jphs.fp0060673
|View full text |Cite
|
Sign up to set email alerts
|

The Elucidation of the Mechanism of Weight Gain and Glucose Tolerance Abnormalities Induced by Chlorpromazine

Abstract: Abstract. Antipsychotic drugs induce weight gain and metabolic abnormalities. Recently, the role of adipocytokines secreted from adipocytes in the development of metabolic syndrome has received attention. The aim of this study was to investigate the effects of chlorpromazine (Cp) on body weight, glucose, lipid metabolism, and adipocytokine secretion in rats fed sucrose. Wistar rats received 15% sucrose (Suc group), 15% sucrose and Cp at 7.5 mg / kg per day (Suc + Cp group), or Cp alone (Cp group) in water for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Insulin resistance could ensue secondary to weight gain, change in body fat composition, or could be due to a direct effect of the antipsychotics on insulin sensitivity (American Diabetes Association 2004; Amamoto et al 2006). Data are again scant in children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin resistance could ensue secondary to weight gain, change in body fat composition, or could be due to a direct effect of the antipsychotics on insulin sensitivity (American Diabetes Association 2004; Amamoto et al 2006). Data are again scant in children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Since visceral fat tissue secretes various physiologically active substances, we determined plasma IL-6 levels, but there was no significant increase in the HFDS-SHHR compared to the SHHR-control and HFDS-SD. Amamoto et al reported that Wister rats that ingested a 15% sucrose solution for 10 weeks showed a significant increase in visceral fat weight with increases in plasma blood glucose, insulin, leptin, and adiponectin, but not plasma TNF-α and IL-6 (27). Therefore, a further experiment to determine other adipocytokines is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…11,49,69,70 Since they were introduced to the clinics in the 1950s, chlorpromazine and thioridazine have been repeatedly reported to cause abnormal glucose tolerance, insulin resistance and even T2DM. [70][71][72][73][74][75][76] On the other hand, it was generally believed that haloperidol did not increase the risk of insulin resistance and T2DM, 49 however recent evidence from clinical trials in first episode patients showed that haloperidol may have a higher risk than originally thought. As discussed above, the EUFEST study has reported that one year treatment of haloperidol has a similar incident rate of hyperglycemia and increased fasting insulin levels to atypical APDs olanzapine and quetiapine.…”
Section: -68mentioning
confidence: 99%